Pef polymeric materials, methods of making and using the same
Patent Information
- Application Number
- CN202611095333.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-22
- Publication Date
- 2026-10-20
AI Technical Summary
PEF分子链中的呋喃环氧原子与酯基羰基氧的配位活性、空间结构与酰亚胺环存在本质差异,直接套用现有方案易导致配位不稳定、性能提升有限
[0077]1、针对PEF分子链特征进行专属配位设计。基于PEF呋喃杂环sp2氧与酯基羰基氧两类位点,筛选能级与构型匹配的金属离子,形成稳定的多齿螯合结构;解决了传统单齿配位不稳定的问题,构建了稳定可逆的物理交联网络,在提升性能的同时保留了PEF的热塑加工性。实现PEF聚合材料力学强度、热稳定性、气体阻隔性能、紫外阻隔性能的同步提升,且不牺牲可回收性。改性后PEF聚合材料拉伸强度提升52%以上,Tg提升5.6℃以上,氧气阻隔性能提升49%以上,紫外阻隔性能提升333%以上,综合性能远超纯PEF及现有改性PEF材料,可满足高端食品包装、精密电子封装等对材料性能有严苛要求的场景。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer materials, specifically relating to a PEF polymer material, its preparation method, and its application. Background Technology
[0002] Polyethylene furanate (PEF), as a novel bio-based polyester, has shown broad application prospects in packaging, electronics, and chemical industries due to its excellent gas barrier properties, biodegradability, and environmental friendliness, and is considered one of the core materials to replace traditional petroleum-based polyesters (such as PET). However, the rigid structure of the furan ring in the PEF molecular chain results in a tensile strength typically below 100 MPa, insufficient toughness (elongation at break ≤11%), and a glass transition temperature (Tg) of only 85-90℃, making it difficult to meet the requirements of high-temperature processing and use. Furthermore, the free volume control of the PEF molecular chain is challenging. How to improve mechanical properties and heat resistance while maintaining high barrier properties has become a critical technical bottleneck that the industry urgently needs to address.
[0003] To address these issues, existing technologies primarily employ single-modification or simple compound modification strategies, but their limitations are significant. First, while chemical crosslinking modification can improve strength and heat resistance by introducing crosslinking agents, the crosslinking bonds are irreversible, completely sacrificing the recyclability and reprocessing properties of PEF, and easily leading to material embrittlement. Second, physical blending modification (such as elastomer and nanoparticle blending) often suffers from poor compatibility and uneven dispersion, resulting in the sacrifice of other key properties while improving one, making it difficult to adapt to high-end applications.
[0004] While metal coordination modification technology has been applied in materials such as polyimide and PET, its direct application to PEF systems presents significant compatibility issues. The coordination activity and spatial structure of the furan epoxy atom and ester carbonyl oxygen in the PEF molecular chain differ fundamentally from those of the imide ring. Directly applying existing schemes easily leads to coordination instability and limited performance improvement. Furthermore, existing technologies often employ a single metal coordination strategy, which can only construct linear structures with low cross-linking density, failing to form a multidimensional, dense physical cross-linking network, making it difficult to simultaneously optimize mechanical, heat-resistant, and barrier properties. In addition, single metal ions are prone to self-aggregation, resulting in poor material processing performance and reduced appearance quality. Some multi-component blending schemes, lacking molecular-level coordination control mechanisms, are prone to component separation and unstable modification effects, hindering large-scale application.
[0005] In summary, the industry urgently needs a metal coordination modification technology that is compatible with the molecular structure of PEF, which can simultaneously and evenly improve mechanical strength, thermal stability and gas barrier properties while maintaining the bio-based and recyclable characteristics of PEF, thus filling the technological gap in the high-end resource utilization of PEF. Summary of the Invention
[0006] To address at least one technical problem existing in the prior art, the present invention aims to provide a PEF polymer material, its preparation method, and its applications. To this end, the present invention provides the following technical solution.
[0007] According to a first aspect of the present invention, a PEF polymeric material is provided, characterized in that the polymeric material comprises PEF and metal ions, wherein the metal ions form a coordinated bond with electron-rich oxygen atoms carrying lone pairs of electrons on the PEF molecular chain; the electron-rich oxygen atoms are distributed in the furan ring and / or ester group structure of PEF.
[0008] This invention regulates the density and stability of the coordination network through synergistic effects. By utilizing the crystal field stabilization energy (CFSE) of metal ions and the Jahn-Teller effect, it ensures that the coordination bonds do not decompose at the conventional processing temperature of PEF (230-280℃), thus guaranteeing performance stability during processing.
[0009] Preferably, the metal ion is a divalent and / or trivalent metal ion;
[0010] Preferably, the metal ions include transition metal ions;
[0011] Preferably, the transition metal ion includes Cu. 2+ Zn 2+ Ni 2+ Ag + One or more of the following, preferably Cu 2+ Zn 2+ Ag + One or more of the following;
[0012] Preferably, the metal ions include alkaline earth metal ions;
[0013] Preferably, the alkaline earth metal ions include Mg. 2+ Ca 2+ One or more of the following;
[0014] Preferably, the metal ions include rare earth metal ions;
[0015] Preferably, the rare earth metal ions include Eu. 3+ 、Tb 3+ One or more of them.
[0016] Preferably, the molar coordination ratio of the metal ion to the PEF repeating unit is 1:(5-40), for example, it can be 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19, 1:20, 1:25, 1:30, 1:35, 1:40 or any value between them; preferably 1:(10-20).
[0017] This ratio range allows for optimized control of coordination network density—below 1:20, there are insufficient coordination crosslinking points, resulting in a weak performance improvement; above 1:5, metal ions tend to agglomerate, leading to material embrittlement and deterioration of processing performance.
[0018] In this invention, the coordination modes specifically include two forms: ① a single metal ion simultaneously chelates two oxygen atoms of a homogeneous furan ring, forming a stable five-membered chelate ring; ② a single metal ion bridges the coordination sites (furan ring oxygen atoms or carboxyl oxygen atoms) of two different PEF molecular chains, constructing a three-dimensional cross-linked network. The synergistic existence of these two modes endows the cross-linked network with good dynamic reversibility, ensuring the material's recyclability and reprocessing performance. The interaction mechanism between metal ions and PEF in this invention is as follows: Figure 4-5 As shown.
[0019] Preferably, the PEF branches also have coordinating groups;
[0020] Preferably, the coordinating group includes one or more of pyridinyl, imidazolyl, carboxyl (-COOH) or β-diketone structures, and is more preferably pyridinyl and / or carboxyl.
[0021] Preferably, the coordinating groups are pyridyl and carboxyl groups, and the molar ratio is 1:(1-3), for example, it can be 1:1, 1:1.5, 1:2, 1:2.5, 1:3 or any value between them.
[0022] In this invention, the coordination activity of the coordinating group is higher than that of the furan epoxy atom, and it can preferentially form highly stable coordination bonds with metal ions (such as Cu). 2+ -Pyridine coordination bond energy >200 kJ / mol) further enhances the stability and compactness of the coordination network through the synergistic effect of "side chain anchoring-main chain crosslinking", while improving the dispersion uniformity of metal ions in the PEF matrix and avoiding agglomeration defects.
[0023] Preferably, the polymeric material further includes a reinforcing body;
[0024] Preferably, the reinforcing body comprises metal-organic frameworks (MOFs) and / or polyhedral oligomeric silsesquioxanes (POSS) with surface-grafted metal ions.
[0025] Preferably, while maintaining the same performance, the amount of metal ions used after adding POSS is reduced by 30% to 50% compared to the system without POSS.
[0026] Preferably, the MOFs include ZIF-8; wherein, the metal nodes of ZIF-8 (Zn 2+ MOFs can form coordination bonds with furan epoxy atoms in the PEF molecular chain, achieving chemical bonding between MOFs and the PEF matrix, rather than simple physical blending. This not only improves gas barrier performance but also regulates molecular chain movement through the porous structure of MOFs, thereby improving heat resistance.
[0027] Preferably, the POSS comprises octavinyl POSS; wherein metal ions (such as Zn) are grafted onto the surface of the octavinyl POSS. 2+ Cu 2+ It can bind to the coordination sites of PEF molecular chains, and the cage-like structure of POSS can enhance the mechanical strength and dimensional stability of the material.
[0028] Preferably, the particle size of the reinforcing material is 50-300 nm, for example, it can be 50 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm or any value between them;
[0029] Preferably, the mass ratio of the reinforcement to PEF is (0.5-3):100, for example, it can be 0.5:100, 1:100, 1.5:100, 2:100, 2.5:100, 3:100 or any value between them.
[0030] Preferably, the performance indicators of the polymeric material include: tensile strength ≥152MPa, elongation at break ≥13%, glass transition temperature (Tg) ≥94.3℃, 5% weight loss temperature (Td,5) ≥396.9℃, oxygen permeability coefficient ≤0.025ml(g)·mm / m²·d·MPa, and ultraviolet barrier factor (UPF) ≥286+.
[0031] According to a second aspect of the present invention, a method for preparing the polymeric material described in the first aspect is provided, comprising the following steps:
[0032] 1) PEF and metal salt were dissolved in polar aprotic solvents to obtain PEF solution and metal salt solution respectively; then the metal salt solution was slowly added dropwise to the PEF solution, and then stirred in the dark to obtain the complexation reaction solution;
[0033] 2) Pour the coordination reaction solution into the film-forming mold, place it in a vacuum drying oven for stepwise heating and curing, and cool it to room temperature after curing.
[0034] Preferably, in step 1), the polar aprotic solvent includes one or more of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), or N,N-dimethylacetamide (DMAc), with DMF being preferred;
[0035] Preferably, the moisture content of the PEF is ≤0.05wt%;
[0036] Preferably, the PEF is stirred at 60-80°C (e.g., 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C, 80°C or any value between them) until it is completely dissolved in a polar aprotic solvent.
[0037] Preferably, the PEF is stirred under a protective atmosphere until it is completely dissolved in a polar aprotic solvent;
[0038] Preferably, the atmosphere includes one or more of nitrogen, argon, helium, and radon;
[0039] Preferably, the concentration of the PEF solution is 5-10 wt%, for example, it can be 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt% or any value between them;
[0040] Preferably, the metal salt comprises metal ions;
[0041] Preferably, the metal ions include transition metal ions;
[0042] Preferably, the transition metal ion includes Cu. 2+ Zn 2+ Ni 2+ Ag + One or more of the following, preferably Cu 2+ Zn 2+ Ag + One or more of the following;
[0043] Preferably, the metal ions include alkaline earth metal ions;
[0044] Preferably, the alkaline earth metal ions include Mg. 2+ Ca 2+ One or more of the following;
[0045] Preferably, the metal ions include rare earth metal ions;
[0046] Preferably, the rare earth metal ions include Eu. 3+ 、Tb 3+ One or more of the following;
[0047] Preferably, the metal salt includes one or more of copper acetate, zinc chloride, and silver nitrate;
[0048] Preferably, the concentration of the metal salt solution is 0.05-0.2 mol / L, for example, it can be 0.05 mol / L, 0.075 mol / L, 0.1 mol / L, 0.125 mol / L, 0.15 mol / L, 0.175 mol / L, 0.2 mol / L or any value between them;
[0049] Preferably, the dripping rate in step 1) is 1-3 mL / min, for example, it can be 1 mL / min, 1.5 mL / min, 2 mL / min, 2.5 mL / min, 3 mL / min or any value between them;
[0050] Preferably, the stirring time in the dark is 4-6 hours, for example, it can be 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours or any value between them.
[0051] Preferably, in step 2), the stepped temperature curing includes processes of 80℃ / 2h, 120℃ / 1h, 200℃ / 1h, and 300℃ / 1h.
[0052] Preferably, the stepped temperature curing is carried out under a protective atmosphere;
[0053] Preferably, the atmosphere includes one or more of nitrogen, argon, helium, and radon;
[0054] Preferably, the stepped temperature curing is carried out under light-protected conditions.
[0055] Preferably, step 1) further includes the step of dissolving the reinforcing material in a polar aprotic solvent, wherein the reinforcing material is MOFs, to obtain an MOFs solution;
[0056] Preferably, the polar aprotic solvent includes one or more of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), or N,N-dimethylacetamide (DMAc), with DMF being the most preferred;
[0057] Preferably, when the reinforcing agent is MOFs, the MOFs solution and PEF solution are mixed to obtain a mixed solution, and the metal salt solution is added dropwise to the mixed solution;
[0058] Preferably, when the reinforcing agent is POSS, POSS is first pre-coordinated with metal ions to obtain a POSS-metal ion complex;
[0059] Preferably, the molar ratio of POSS to metal salt is 1:(2-4), for example, it can be 1:2, 1:2.5, 1:3, 1:3.5, 1:4 or any value between them.
[0060] Preferably, the step of dissolving the reinforcing agent in a polar aprotic solvent specifically includes:
[0061] (1) Reinforcement pretreatment: If MOFs are used for reinforcement, ZIF-8 nanoparticles are vacuum dried at 80°C for 4 hours, dispersed in a polar aprotic solvent and sonicated for 30 minutes to form a ZIF-8 dispersion with a concentration of 0.5-1wt%.
[0062] If POSS reinforcement is used, octavinyl POSS is mixed with metal salt in a molar ratio of 1:(2-4), and stirred at 60°C for 2 hours to obtain POSS-metal ion complex;
[0063] (2) Coordination reaction: After dissolving PEF powder to form a 5-10 wt% solution, add ZIF-8 dispersion or POSS-metal ion complex, stir evenly, add the remaining metal salt solution, stir in the dark for 4-6 hours to obtain the coordination reaction solution.
[0064] Preferably, the preparation method further includes a PEF raw material pretreatment step.
[0065] Preferably, the PEF raw material pretreatment specifically includes the following steps:
[0066] Place the PEF powder in a vacuum drying oven and dry it at 100-120℃ for 8-12 hours to avoid moisture affecting the coordination reaction activity.
[0067] Preferably, when the PEF branches have coordinating groups, the preparation method includes the following steps:
[0068] a) Synthesis of functional monomers: Using 2,5-furandicarboxylic acid (FDCA) as a raw material, FDCA derivative monomers containing reinforcing coordination groups (carboxyl or pyridyl) are synthesized through acylation and substitution reactions, with a purity ≥99.5%;
[0069] b) Preparation of functionalized PEF: FDCA derivative monomer, FDCA, and ethylene glycol are mixed in a molar ratio of 0.1-0.3:0.7-0.9:1.2-1.5. A composite catalyst (tetrabutyl titanate and antimony catalyst are mixed in a mass ratio of 1:1) and an antioxidant are added. Esterification reaction is carried out at 220-250℃ and 35-56 kPa. After the esterification rate is ≥90%, the temperature is raised to 255-262℃ and polycondensation reaction is carried out under vacuum to obtain PEF with coordinating groups in the side chain.
[0070] Preferably, the method includes the following steps:
[0071] (1) Raw material pretreatment: PEF powder is vacuum dried at 100-120℃ for 8-12 hours, and the moisture content is controlled to be ≤0.05wt%; soluble metal salts are dissolved in polar aprotic solvents to prepare metal salt solutions with a concentration of 0.05-0.2mol / L;
[0072] (2) Coordination reaction: Dissolve the dried PEF powder in a polar aprotic solvent and stir at 60-80℃ under nitrogen protection until completely dissolved to form a 5-10 wt% PEF solution; slowly add the metal salt solution dropwise to the PEF solution at a molar ratio of 1-3 mL / min. After the addition is complete, stir in the dark for 4-6 hours to obtain the coordination reaction solution.
[0073] (3) Step-by-step curing: Pour the coordination reaction solution into the film forming mold, place it in a vacuum drying oven, and cure it in an inert atmosphere by step-by-step heating as follows: 80℃ / 2h→120℃ / 1h→200℃ / 1h→300℃ / 1h; after cooling to room temperature, demold to obtain the target material.
[0074] According to a third aspect of the present invention, the application of the polymeric material described in the first aspect or the polymeric material prepared by the preparation method described in the second aspect is provided.
[0075] Preferably, the applications include, but are not limited to, the preparation of high-end food packaging materials, precision electronic packaging materials, gas separation membranes, or high-temperature resistant engineering components.
[0076] Compared with the prior art, the present invention has at least the following beneficial technical effects:
[0077] 1. Specific coordination design tailored to the characteristics of the PEF molecular chain. Based on the two types of sites in PEF furan heterocycles (sp2 oxygen and ester carbonyl oxygen), metal ions with matching energy levels and configurations are screened to form a stable multidentate chelate structure. This solves the problem of instability in traditional monodentate coordination, constructing a stable and reversible physical cross-linking network, improving performance while retaining the thermoplastic processability of PEF. This achieves simultaneous improvement in the mechanical strength, thermal stability, gas barrier properties, and UV barrier properties of PEF polymer materials without sacrificing recyclability. The modified PEF polymer material exhibits a tensile strength increase of over 52%, a Tg increase of over 5.6℃, an oxygen barrier property increase of over 49%, and a UV barrier property increase of over 333%. Its overall performance far surpasses that of pure PEF and existing modified PEF materials, meeting the stringent performance requirements of high-end food packaging, precision electronic packaging, and other applications.
[0078] 2. A multi-metal hierarchical synergistic coordination strategy is adopted, utilizing three types of functionally differentiated metal ions to achieve site-specific synergy: highly furan ring-selective ions fix the rigid structure, improving heat resistance and barrier properties; highly ester-selective ions bridge the molecular chains, achieving "reinforcement and toughening"; and ions with both weak coordination and nucleation functions are used to supplement network defects and induce crystallization. The construction of a multi-dimensional dense network achieves simultaneous improvement in mechanical, heat resistance, and barrier properties.
[0079] 3. To address the challenges of competitive coordination and aggregation that easily occur in multi-metal complexes, this application thermodynamically matches differentiated metal combinations and kinetically innovates a stepwise coordination process (first constructing a basic network through low-activity bridging, then performing high-activity chelation for site-specific coordination). This approach is compatible with existing general-purpose melt processing equipment, has a wide process window, good batch repeatability, overcomes the technical barriers of multi-metal coordination, and is ready for large-scale application. Attached Figure Description
[0080] Figure 1 The chemical structure and proton NMR spectrum of Comparative Example 1 (pure PEF) are shown below. The letters in the chemical structure correspond one-to-one with the peaks in the NMR spectrum. The NMR spectrum was prepared using deuterated trifluoroacetic acid as the solvent (chemical shift δ = 11.5 ppm) and clearly shows the molecular structure characteristics of pure PEF.
[0081] Figure 2 The images show a comparison of the film appearance of Example 2 (PEFC15) and Comparative Example 1 (pure PEF). The left image shows the PEFC15 film, which exhibits a uniform colored luster due to the coordination of metal ions and has no agglomeration defects. The right image shows the pure PEF film, which is colorless and transparent and has no special optical properties.
[0082] Figure 3 This is a diagram showing the transparent coating effect of the film in Comparative Example 1 (pure PEF). The film has good transparency, but its UV blocking performance and mechanical properties are poor, which cannot meet the comprehensive requirements of high-end packaging.
[0083] Figure 4 This is a diagram illustrating the interaction mechanism of the metal-coordinated PEF of this invention.
[0084] Figure 5 This is a schematic diagram illustrating the mechanism of action of the metal-coordinated PEF of the present invention. Detailed Implementation
[0085] The present invention will be further illustrated below through embodiments. It should be understood that the embodiments of the present invention are only for illustrating the present invention and not for limiting the present invention. Simple improvements to the present invention under the premise of the concept of the present invention are all within the scope of protection claimed by the present invention.
[0086] Experimental materials
[0087] PEF powder: intrinsic viscosity 0.622 dl / g, commercially available;
[0088] FDCA: 99.8% purity, commercially available;
[0089] FDCA derivative monomers containing pyridyl groups: self-made, purity 99.6%;
[0090] Metal salts: copper acetate, zinc chloride, silver nitrate, magnesium acetate, and nickel acetate, all of analytical grade;
[0091] Polar aprotic solvents: DMF, NMP, DMAc, all of analytical grade;
[0092] ZIF-8 nanoparticles: 200nm particle size, commercially available;
[0093] Octadecyl POSS: 99% purity, commercially available;
[0094] Composite catalyst: Tetrabutyl titanate and antimony trioxide are mixed in a mass ratio of 1:1;
[0095] Antioxidant: 1010 and 168 are compounded in a 1:1 mass ratio.
[0096] Performance testing standards or methods
[0097] 1. Intrinsic viscosity ([η]): Tested according to GB / T 14190-2008;
[0098] 2. Melt Flow Index (MFI): Tested according to GB / T 3682-2018, test temperature 260℃;
[0099] 3. Crystallinity (Xc): Tested according to GB / T 19466.3-2004 (DSC method), heating rate 10℃ / min;
[0100] 4. Tensile properties: Tested according to GB / T 1040.2-2006, tensile rate 50 mm / min, test temperature 23℃;
[0101] 5. Thermal stability: Tested according to GB / T 19466.6-2009 (TGA method), under nitrogen atmosphere, heating rate 10℃ / min, Td,5 is the 5% weight loss temperature;
[0102] 6. Glass transition temperature (Tg): Tested according to GB / T 19466.3-2004 (DSC method);
[0103] 7. Oxygen gas permeability coefficient: tested according to GB / T 1038-2022;
[0104] 8. Ultraviolet blocking factor (UPF): Tested according to GB / T 18830-2009;
[0105] 9. Conductivity: Tested according to GB / T 1410-2006.
[0106] Example
[0107] Example 1, 1. Raw material pretreatment: PEF powder was vacuum dried at 120℃ for 10 hours; copper acetate was dissolved in DMF to prepare a 0.1 mol / L copper acetate solution;
[0108] 2. Coordination reaction: Dissolve PEF powder in DMF and stir at 70°C under nitrogen protection until dissolved to form an 8wt% PEF solution; according to the molar ratio of metal salt to repeating PEF unit (the repeating unit of PEF is C... 10 H8O4, with a molar mass of approximately 192.16 g / mol. A copper acetate solution was slowly added dropwise to PEF solution at a ratio of 1:20, with a dropping rate of 2 mL / min, and stirred in the dark for 5 hours.
[0109] 3. Step curing: Curing at 80℃ / 2h→120℃ / 1h→200℃ / 1h→300℃ / 1h (nitrogen atmosphere), and demolding to obtain PEFC20 material.
[0110] Performance test results: [η] = 0.607 dL / g, MFI = 20 g / 10 min, Xc = 16%, ρs = 1.465 g / cm³ 3 Tg = 102.5℃, Td,5 = 399.1℃, elongation at break = 13%, oxygen permeability coefficient = 0.0092 ml (g)·mm / m 2 ·d·MPa, UPF=286+, electrical conductivity=0.076S / cm; tensile strength=152MPa, which is 52% higher than that of pure PEF.
[0111] Example 2, the preparation steps are the same as in Example 1, except that the molar ratio of copper acetate metal salt to PEF repeating unit is 1:15, to obtain PEFC15 material.
[0112] Performance test results: [η] = 0.616 dL / g, MFI = 19 g / 10 min, Xc = 35%, ρs = 1.467 g / cm³ 3 Tg = 106.8℃, Td,5 = 404.1℃, elongation at break = 17%, oxygen permeability coefficient = 0.0055 ml (g)·mm / m 2 ·d·MPa, UPF=299+, electrical conductivity=0.091S / cm; tensile strength=168MPa, which is 68% higher than pure PEF and has the best overall performance.
[0113] Example 3, 1. Synthesis of functional monomers: Using FDCA as a raw material, pyridyl-containing FDCA derivative monomers were synthesized via acylation and pyridyl substitution reactions; the equations are as follows:
[0114] .
[0115] 2. Preparation of Functionalized PEF: The derivative monomer, FDCA, and ethylene glycol were mixed in a molar ratio of 0.2:0.8:1.3, and a composite catalyst and antioxidant were added. Esterification was carried out at 230℃ and 45 kPa (esterification rate 92%), followed by polycondensation under vacuum at 258℃ to obtain functionalized PEF (b-PEF) with pyridine groups in the side chain; the equation is as follows:
[0116] .
[0117] 3. Coordination film formation: b-PEF is dissolved in DMF to form an 8wt% solution. Nickel acetate solution is added at a molar ratio of nickel acetate metal salt to PEF repeating unit of 1:15. The mixture is stirred in the dark for 5 hours and then cured in a stepwise manner to obtain b-PEFN15 material.
[0118] Performance test results: [η] = 0.623 dL / g, MFI = 14 g / 10 min, Xc = 49%, ρs = 1.488 g / cm³ 3 Tg = 101.3℃, Td,5 = 405.2℃, elongation at break = 15%, oxygen permeability coefficient = 0.0093 ml (g)·mm / m 2 ·d·MPa, UPF=362+, electrical conductivity=0.098S / cm; tensile strength=172MPa, which is 72% higher than pure PEF and has the best coordination stability.
[0119] Example 4, 1. Pretreatment of nano-reinforcement: ZIF-8 nanoparticles were vacuum dried at 80°C for 4 hours, dispersed in DMF, and sonicated for 30 minutes to form a 0.8wt% ZIF-8 dispersion;
[0120] 2. Complex coordination reaction: PEF is dissolved in DMF to form an 8wt% solution, and ZIF-8 (zinc salt) dispersion (ZIF-8 to PEF mass ratio 1:100) is added. After stirring evenly, zinc chloride solution is added at a ZIF-8 to PEF repeating unit molar ratio of 1:15. Stir for 5 hours in the dark.
[0121] 3. Step curing: Curing was performed according to the process in Example 1 to obtain PEFZM15 material.
[0122] Performance test results: [η] = 0.596 dL / g, MFI = 19 g / 10 min, Xc = 39%, ρs = 1.471 g / cm³3 Tg = 94.3℃, Td,5 = 396.9℃, elongation at break = 21%, oxygen permeability coefficient = 0.025 ml (g)·mm / m 2 ·d·MPa, UPF=311+, electrical conductivity=0.081S / cm; tensile strength=158MPa, 58% higher than pure PEF, with the best toughness.
[0123] Example 5, 1. Pretreatment of nano-reinforcement: ZIF-8 nanoparticles were vacuum dried at 80°C for 4 hours, dispersed in DMF, and sonicated for 30 minutes to form a 0.8wt% ZIF-8 dispersion;
[0124] 2. Complex coordination reaction: PEF is dissolved in DMF to form an 8wt% solution, silver nitrate dispersion (silver nitrate to PEF mass ratio 1:100) is added, and after stirring evenly, silver acetate solution is added according to the repeating unit molar ratio of silver nitrate to PEF 1:15, and the mixture is stirred in the dark for 5 hours.
[0125] 3. Step curing: Curing was performed according to the process in Example 1 to obtain PEFAg15 material.
[0126] Performance test results: [η] = 0.536 dL / g, MFI = 21 g / 10 min, Xc = 36%, ρs = 1.470 g / cm³, Tg = 94.1℃, Td,5 = 396.1℃, elongation at break = 22%, oxygen permeability coefficient = 0.0243 ml (g)·mm / m 2 ·d·MPa, UPF=350+, electrical conductivity=0.092S / cm; tensile strength=153MPa, which is 53% higher than that of pure PEF.
[0127] Example 6, 1. Raw material pretreatment: PEF powder was vacuum dried at 120℃ for 10 hours; magnesium acetate was dissolved in DMF to prepare a 0.1 mol / L copper acetate solution;
[0128] 2. Coordination reaction: PEF powder was dissolved in DMF and stirred at 70°C under nitrogen protection until dissolved to form an 8wt% PEF solution; magnesium acetate solution was slowly added dropwise to PEF solution at a drop rate of 2mL / min at a molar ratio of 1:15 to the repeating unit of PEF, and stirred in the dark for 5 hours.
[0129] 3. Step curing: Curing at 80℃ / 2h → 120℃ / 1h → 200℃ / 1h → 300℃ / 1h (nitrogen atmosphere), and demolding to obtain PEFM15 material.
[0130] Performance test results: [η] = 0.622 dL / g, MFI = 18 g / 10 min, Xc = 23%, ρs = 1.466 g / cm³3 Tg = 101.7℃, Td,5 = 399.3℃, elongation at break = 14%, oxygen permeability coefficient = 0.0099 ml (g)·mm / m 2 ·d·MPa, UPF=293+, electrical conductivity=0.071S / cm; tensile strength=151MPa, which is 52% higher than that of pure PEF.
[0131] Comparative Example 1
[0132] Preparation steps: Mix FDCA (500g, 3.2mol), compound catalyst (160ppm), and antioxidant (500ppm) evenly; dissolve ether stabilizer (20ppm) in ethylene glycol (4mol); add the above materials to a 2.5L reactor, stir at room temperature for 30 minutes, and replace with inert gas 3 times; perform esterification reaction at 160-195℃ and 35-56Kpa (esterification rate >90%), pre-condense under vacuum at 200-235℃ for 50 minutes, and final condense under vacuum at 255-262℃ for 27 minutes, then granulate and dry to obtain pure PEF material.
[0133] Performance test results: [η] = 0.585 dL / g, MFI = 26 g / 10 min, Xc = 6%, ρs = 1.460 g / cm³ 3 Tg = 88.7℃, Td,5 = 376.5℃, elongation at break = 11%, oxygen permeability coefficient = 0.011 ml (g)·mm / m 2 ·d·MPa, UPF=66+, electrical conductivity=0.002S / cm; tensile strength=100MPa.
[0134] Comparative Example 2
[0135] Preparation steps: PEF is dissolved in DMF to form an 8wt% solution. Copper acetate solution is added at a molar ratio of metal salt to PEF repeating unit of 1:15. The mixture is stirred at room temperature for 5 hours and then directly cured at 200℃ to form a film (stepless curing process).
[0136] Performance test results: [η] = 0.572 dL / g, MFI = 23 g / 10 min, Xc = 22%, ρs = 1.462 g / cm³ 3 Tg = 95.3℃, Td,5 = 382.1℃, elongation at break = 8%, oxygen permeability coefficient = 0.010 ml (g)·mm / m 2 ·d·MPa, UPF=150+, electrical conductivity=0.065S / cm; tensile strength=125MPa, which is 25% higher than pure PEF, but the improvement in toughness and heat resistance is limited, and there are local metal ion agglomeration defects.
[0137] Comparative Example 3
[0138] Preparation steps: PEF powder and POE-g-MAH are mixed at a mass ratio of 92:8, antioxidants are added, and the mixture is extruded and granulated using a twin-screw extruder at 260°C and then pressed into a film.
[0139] Performance test results: [η] = 0.568 dL / g, MFI = 28 g / 10 min, Xc = 12%, ρs = 1.455 g / cm³ 3 Tg = 87.2℃, Td,5 = 370.3℃, elongation at break = 18%, oxygen permeability coefficient = 0.019 ml (g)·mm / m 2 ·d·MPa, UPF=80+, conductivity=0.003S / cm; tensile strength=75MPa, a 25% decrease compared to pure PEF, indicating a significant deterioration in barrier performance.
[0140] As can be seen from the above performance test data, the metal coordination reinforced PEF materials prepared in Examples 1-6 of this invention achieve simultaneous and significant improvements in core indicators such as tensile strength, elongation at break, Tg, Td,5, oxygen barrier properties, and ultraviolet barrier properties, and their comprehensive performance far exceeds that of the comparative examples.
[0141] 1. Mechanical properties: The tensile strength of Examples 1-6 is ≥151MPa, which is more than 51% higher than that of pure PEF (100MPa). Among them, Example 3 (side chain functionalization) reaches 172MPa, an improvement of 72%. The elongation at break is ≥13% of all examples, with Example 4 (nanocomposite) reaching 21%, an improvement of 90.9% compared to pure PEF. This solves the problem of existing modification technologies that "toughening inevitably reduces strength" or "strengthening inevitably reduces toughness". In contrast, the tensile strength of Comparative Example 2 (single coordination) is only increased by 25%, and the elongation at break is reduced to 8%. The tensile strength of Comparative Example 3 (physical blend) is reduced by 25%, with only a slight improvement in toughness.
[0142] 2. Thermal stability: The Tg of Examples 1-6 is ≥94.1℃, which is more than 5.6℃ higher than that of pure PEF (88.7℃). Example 2 reaches 106.8℃, an increase of 18.1℃. The Td,5 is ≥396.9℃, which is more than 20℃ higher than that of pure PEF (376.5℃). Example 2 reaches 404.1℃, an increase of 27.6℃, which can meet the requirements of high-temperature processing and use. The Tg of Comparative Example 2 is only increased by 6.6℃, and the Td,5 is only increased by 5.6℃. The Tg and Td,5 of Comparative Example 3 are slightly decreased, and the thermal stability deteriorates.
[0143] 3. Barrier and Functional Performance: The oxygen permeability coefficients of Examples 1-6 are all ≤0.025 ml (g)·mm / m²·d·MPa, with Example 2 reaching 0.0055, which is 49.1% higher than pure PEF and far superior to Comparative Example 3 (0.019); the UPF of all examples is ≥286+, which is more than 333% higher than pure PEF (66+), demonstrating excellent UV blocking function, while the UPF improvement of Comparative Examples 2 and 3 is limited.
[0144] 4. Processing and appearance performance: Examples 1-6 showed no metal ion agglomeration defects, with MFI controlled at 14-20 g / 10 min, and excellent processing fluidity; Comparative Example 2 showed local agglomeration defects and poor processing stability; Comparative Example 3 had MFI increased to 28 g / 10 min, but the melt strength was insufficient, and problems such as sagging and uneven thickness were prone to occur during processing.
[0145] Furthermore, the material of this invention, through dynamic coordination network design, can achieve solvent recovery and reprocessing. After reprocessing, the tensile strength decreases by less than 5%, maintaining good performance stability. In contrast, the performance of Comparative Example 2 (single coordination) decreases by more than 20% after reprocessing, and the performance of Comparative Example 3 (physical blending) decreases by more than 30% after reprocessing, making effective recovery impossible.
[0146] In summary, this invention, through multi-dimensional synergistic enhancement strategies and process innovation, breaks through the inherent limitations of existing technologies, producing PEF materials with excellent comprehensive performance, good recyclability and processing stability, demonstrating significant technical advantages.
[0147] While some exemplary embodiments of this application have been described and illustrated, this application is not limited to the disclosed embodiments. Rather, those skilled in the art will recognize that modifications and changes may be made to the described embodiments without departing from the spirit and scope of this application as described in the appended claims.
Claims
1. A PEF polymer material, characterized in that, The polymeric material includes PEF and metal ions, wherein the metal ions form a coordinated bond with electron-rich oxygen atoms carrying lone pairs of electrons on the PEF molecular chain; the electron-rich oxygen atoms are distributed in the furan ring and / or ester group structure of PEF.
2. The polymeric material according to claim 1, characterized in that, The metal ions are divalent and / or trivalent metal ions; Preferably, the metal ions include transition metal ions; Preferably, the transition metal ion includes Cu. 2+ Zn 2+ Ni 2+ Ag + One or more of the following, preferably Cu 2+ Zn 2+ Ag + One or more of the following; Preferably, the metal ions include alkaline earth metal ions; Preferably, the alkaline earth metal ions include Mg. 2+ Ca 2+ One or more of the following; Preferably, the metal ions include rare earth metal ions; Preferably, the rare earth metal ions include Eu. 3+ 、Tb 3+ One or more of them.
3. The polymeric material according to claim 1 or 2, characterized in that, The metal ion is a transition metal ion, preferably Cu. 2+ ; Preferably, the molar coordination ratio of the metal ion to the PEF repeating unit is 1:(5-40); more preferably, it is 1:(5-20).
4. The polymeric material according to claim 1 or 2, characterized in that, Coordinating groups are also present on the side chains of PEF; Preferably, the coordinating group includes one or more of pyridinyl, imidazolyl, carboxyl (-COOH) or β-diketone structures, and is more preferably pyridinyl and / or carboxyl. Preferably, the coordinating groups are pyridyl and carboxyl groups, and the molar ratio is 1:(1-3).
5. The polymeric material according to claim 1 or 2, characterized in that, The polymeric material further includes a reinforcing agent; Preferably, the reinforcing body comprises metal-organic frameworks (MOFs) and / or polyhedral oligomeric silsesquioxanes (POSS) with surface-grafted metal ions. Preferably, the MOFs include ZIF-8; Preferably, the POSS comprises an octavinyl POSS; Preferably, the particle size of the reinforcing material is 50-300 nm; Preferably, the mass ratio of the reinforcement to PEF is (0.5-3):
100.
6. A method for preparing the polymeric material according to any one of claims 1-5, characterized in that, Includes the following steps: 1) Dissolve PEF and metal salt in polar aprotic solvents respectively to obtain PEF solution and metal salt solution respectively; The metal salt solution was then slowly added dropwise to the PEF solution, followed by stirring in the dark to obtain the coordination reaction solution; 2) Pour the coordination reaction solution into the film-forming mold, place it in a vacuum drying oven for stepwise heating and curing, and cool it to room temperature after curing.
7. The preparation method according to claim 6, characterized in that, In step 1), the polar aprotic solvent includes one or more of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), or N,N-dimethylacetamide (DMAc), preferably DMF; Preferably, the moisture content of the PEF is ≤0.05wt%; Preferably, the PEF is stirred at 60-80°C until it is completely dissolved in a polar aprotic solvent; Preferably, the PEF is stirred under a protective atmosphere until it is completely dissolved in a polar aprotic solvent; Preferably, the atmosphere includes one or more of nitrogen, argon, helium, and radon; Preferably, the concentration of the PEF solution is 5-10 wt%; Preferably, the metal salt comprises metal ions; Preferably, the metal ions include transition metal ions; Preferably, the transition metal ion includes Cu. 2+ Zn 2+ Ni 2+ Ag + One or more of the following, preferably Cu 2+ Zn 2+ Ag + One or more of the following; Preferably, the metal ions include alkaline earth metal ions; Preferably, the alkaline earth metal ions include Mg. 2+ Ca 2+ One or more of the following; Preferably, the metal ions include rare earth metal ions; Preferably, the rare earth metal ions include Eu. 3+ 、Tb 3+ One or more of the following; Preferably, the metal salt includes one or more of copper acetate, zinc chloride, and silver nitrate; Preferably, the concentration of the metal salt solution is 0.05-0.2 mol / L; Preferably, the dropping rate in step 1) is 1-3 mL / min; Preferably, the stirring time in the dark is 4-6 hours.
8. The preparation method according to claim 6, characterized in that, In step 2), the stepped temperature curing process includes: 80℃ / 2h, 120℃ / 1h, 200℃ / 1h and 300℃ / 1h. Preferably, the stepped temperature curing is carried out under a protective atmosphere; Preferably, the atmosphere includes one or more of nitrogen, argon, helium, and radon; Preferably, the stepped temperature curing is carried out under light-protected conditions.
9. The preparation method according to claim 6, characterized in that, Step 1) also includes the step of dissolving the reinforcing material in a polar aprotic solvent, wherein the reinforcing material is MOFs, to obtain an MOFs solution; Preferably, the polar aprotic solvent includes one or more of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), or N,N-dimethylacetamide (DMAc), with DMF being the most preferred; Preferably, when the reinforcing agent is MOFs, the MOFs solution and PEF solution are mixed to obtain a mixed solution, and the metal salt solution is added dropwise to the mixed solution; Preferably, when the reinforcing agent is POSS, POSS is first pre-coordinated with metal ions to obtain a POSS-metal ion complex; Preferably, the molar ratio of POSS to metal salt is 1:(2-4).
10. The use of the polymeric material according to any one of claims 1-5 or the polymeric material prepared by the preparation method according to any one of claims 6-9.